2017
DOI: 10.3390/toxins9110369
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Active Properties of an Amphitropic Peptide from the CyaA Toxin Translocation Region

Abstract: The adenylate cyclase toxin CyaA is involved in the early stages of infection by Bordetella pertussis, the causative agent of whooping cough. CyaA intoxicates target cells by a direct translocation of its catalytic domain (AC) across the plasma membrane and produces supraphysiological levels of cAMP, leading to cell death. The molecular process of AC translocation remains largely unknown, however. We have previously shown that deletion of residues 375–485 of CyaA selectively abrogates AC translocation into euk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 80 publications
2
39
0
4
Order By: Relevance
“…Reverse phase evaporation was used to prepare small unilamellar vesicles (SUVs). A 10 mM lipid solution made of an 8:2 mixture of 1-palmitoyl-2-oleoyl phosphatidylcholine (POPC) and 1-palmitoyl-2-oleoylglycero-3-phosphoglycerol (POPG) (Avanti Polar Lipids) was prepared as described 68 . Chloroform was removed by evaporation under vacuum conditions and the dried phospholipid film was resuspended in a mixture of diethyl ether and buffer (25 mM Hepes pH 7.4, 10 mM MgCl 2 and 150 mM KCl).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse phase evaporation was used to prepare small unilamellar vesicles (SUVs). A 10 mM lipid solution made of an 8:2 mixture of 1-palmitoyl-2-oleoyl phosphatidylcholine (POPC) and 1-palmitoyl-2-oleoylglycero-3-phosphoglycerol (POPG) (Avanti Polar Lipids) was prepared as described 68 . Chloroform was removed by evaporation under vacuum conditions and the dried phospholipid film was resuspended in a mixture of diethyl ether and buffer (25 mM Hepes pH 7.4, 10 mM MgCl 2 and 150 mM KCl).…”
Section: Methodsmentioning
confidence: 99%
“…The KaleidaGraph software was used to fit the K x to the experimental data (for details, see ref. 68 ).…”
Section: Methodsmentioning
confidence: 99%
“…The preferential binding of P454 to calmodulin over membrane was confirmed by a lipid vesicle permeabilization assay 63,65 . In this set up, addition of P454 peptide to ANTS:DPX loaded vesicles induces membrane permeabilization leading to a dye efflux that is monitored by fluorescence increase as a result of ANTS dequenching.…”
Section: -The P454 Peptide From the Cyaa Toxin Binds To Calmodulinmentioning
confidence: 94%
“…However, the molecular mechanism and forces involved in the translocation of the CyaA catalytic domain across the plasma membrane have thus far remained elusive. We have previously shown that a peptide, corresponding to the C-terminus of the translocation region TR of CyaA, P454 (residues 454-484, Figure S1), exhibits membrane-active properties related to antimicrobial peptides (AMPs) 17,63 : this peptide adopts a helical conformation upon membrane interaction and induces a local destabilization of the lipid bilayer [63][64][65][66] . This property is likely essential for CyaA as deletion of the TR region (residues 384-489) encompassing the P454 segment, selectively abrogates the ability of the modified toxin to intoxicate target cells 17 .…”
Section: Introductionmentioning
confidence: 99%
“…CyaA is a large, multidomain protein of 1706 amino-acid residues, with AC (residues 1-364) (16), whereas the C-terminal hemolysin region (residues 365-1706) contains several domains responsible for AC membrane translocation and pore-forming activity (19)(20)(21)(22)(23)(24). The translocation region (TR; residues 365-527) is involved in AC translocation across target cell membranes (24) and membrane permeabilization (25) and exhibits features similar to membrane-active peptides (24,26,27). The hydrophobic region (HR) corresponds to residues 528-710, whereas the acylation region (AR) extends from residues 711 through 1005.…”
mentioning
confidence: 99%